Critical realism, post-keynesian economic and the sraffian question - Pringle, David (Université d'Ottawa | University of Ottawa, 2003)
The aim of this essay is threefold: to explain critical realism as it applies to economics, to consider critical realism as the methodological foundation for post-Keynesian economics and to assess whether or not the Sraffian approach is compatible within